Hifz al-‘Aql and the Brain Rot Phenomenon in Digital Content Consumption - Ana Nurwakhidah; Lulud Wijayanti (Yayasan Pendidikan Islam Bustanul Ulum Mojokerto, 2026)
Brain rot caused by excessive digital content consumption from the perspective of hifz al-‘aql (preservation of intellect) within the framework of Maqasid al-Shariah. The rapid expansion of short-form digital media such as TikTok, Instagram Reels, and YouTube Shorts has significantly transformed human cognitive behavior, attention patterns, emotional regulation, and consumption habits. While digital media provide educational, informational, and economic opportunities, excessive exposure to algorithm-driven entertainment content contributes to cognitive fatigue, declining concentration, emotional instability, shortened attention spans, procrastination, and digital addiction. This research employs a qualitative library research approach grounded in Islamic epistemology and Islamic behavioral economics by analyzing Qur’anic verses, Hadith, classical Islamic scholarship, and contemporary studies on digital addiction and attention economy. The findings indicate that brain rot contradicts the objective of hifz al-‘aql because it weakens critical thinking, self-control, intellectual productivity, and reflective consciousness while promoting impulsive, passive, and hedonic behavior. Furthermore, the research reveals that algorithmic digital culture commodifies human attention and encourages excessive entertainment consumption at the expense of intellectual and spiritual development. Islamic behavioral economics offers an ethical framework emphasizing moderation (wasatiyyah), self-discipline (mujahadah al-nafs), ethical consumption, time accountability, and spiritually guided digital engagement to preserve intellectual well-being in the digital era. The research also proposes a maqasid-based digital consumption framework integrating cognitive protection, ethical media use, and spiritual awareness as preventive strategies against digital addiction and cognitive degradation. This research contributes theoretically to the development of Islamic behavioral economics and Islamic digital ethics while practically offering guidance for ethical digital literacy and healthy technology consumption among Muslim societies.